Addressing the Сompetence of Experts and Specialists in the Light of Provisions of ISO/IEC 17025:2017 and International Experience in Applying Specialized Knowledge - E. V. Chesnokova; R. S. DuVal (Теория и практика судебной экспертизы, 2019)
The purpose of the study is to reflect differences in approaches to determining the competence of experts and specialists in domestic forensic expertise and based on international standards for forensic examination. According to the international standard, ISO/IEC 17025:2017 “General requirements for the competence of testing and calibration laboratories”, competence is determined by the demonstrated ability to apply knowledge and/or skills and personal qualities. An attempt has been made to adapt this formulation to the realities of the Russian forensic activities. Also – based on a standard approach – consideration has been given to the issue of specialized knowledge in the field of trades and crafts, as well as opportunities to determine the level of expertise have been discussed considering two possible professional situations: individuals who have passed state certification procedures relating to their trades or crafts, and individuals working in their trades or crafts without having received such certification. International standards for forensic examination and comments thereto, foreign expert practice, publications on domestic forensic expertise and the procedural codes of the Russian Federation have served as materials for the research. The methods of the general theory of forensic examination have been used in the process of research, which are comparative analysis, abstraction and modeling and legal analysis. Regarding people with special knowledge the international standard ISO/IEC 17025:2017 “General requirements for the competence of testing and calibration laboratories” demonstrates the breadth and universality of an approach to their competent activity. What is important here is the demonstrated ability to apply knowledge and/or skills, as shown by a specialist or expert at the time of competence assessment or verification within the framework of forensic laboratory accreditation. A situation when there is equality of knowledge and/or skills and personal qualities can be adapted (to some extent and without significant adjustments) to the Russian realities in forensic activities. For example, in areas of application of specialized knowledge such as skilled trades or crafts or in narrowly specialized or rare spheres of human activity. The various formulations of the term “competence” contain one unchanging feature – the obligatory verification of the level of knowledge and skills. The mechanisms that have been developed through practice to verify the competence of experts and specialists can be supplemented by the capabilities provided by standards. Assessing an expert’s competence taking into account the processes of standardization in forensic activities, currently pending updates to legislation on forensic activities in the Russian Federation and also foreign experience in the application of specialized knowledge in courts of the USA, will contribute to the formation of an integrated position of the Russian expert community and a better implementation of standardization into domestic science, as well as of the unification of rules for the forensic expert activity.